2020
DOI: 10.2196/17361
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Internet-Based Electronic Technology Interventions on Breastfeeding Outcomes: Systematic Review

Abstract: Background Supporting women to initiate and continue breastfeeding is a global challenge. A range of breastfeeding interventions employing electronic technologies (e-technologies) are being developed, which offer different delivery modes and features over the internet; however, the impact of internet-based e-technologies on breastfeeding outcomes remains unclear. Objective This study aimed to identify the characteristics of current internet-based breast… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 69 publications
4
36
0
4
Order By: Relevance
“…It has been demonstrated that information and communication systems, such as web platform, mobile apps, and SMS can be used to promote, educate, and support breastfeeding women, and offer effective means of improving breastfeeding outcomes [ 33 , 34 ]. From 2010 to 2012, a study in Shanghai using SMS to promote breastfeeding found that weekly messages on infant feeding from the third trimester to 12 months postpartum could improve the exclusive breastfeeding rate at 6 months (OR 2.67) but not at 4 months [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that information and communication systems, such as web platform, mobile apps, and SMS can be used to promote, educate, and support breastfeeding women, and offer effective means of improving breastfeeding outcomes [ 33 , 34 ]. From 2010 to 2012, a study in Shanghai using SMS to promote breastfeeding found that weekly messages on infant feeding from the third trimester to 12 months postpartum could improve the exclusive breastfeeding rate at 6 months (OR 2.67) but not at 4 months [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Developing and applying effective educational programs for improving breastfeeding self-efficacy (BSE) are important concerns for health professionals, and it can help mothers initiate and maintain breastfeeding for six months after birth [ 7 , 8 ]. In particular, breastfeeding educational programs have shown a positive effect on maternal breastfeeding behavior, awareness and attitude toward breastfeeding, continuity of breastfeeding, and BSE of mothers at six months after childbirth recently [ 5 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the importance and the need to combine educational strategies since prenatal care that offer support for the maintenance of exclusive breastfeeding and that take these factors into account is highlighted. 8 The sociodemographic factors indicate that early weaning occurred in women with a mean age of 26 years, complete high school education, and paid occupation, i.e., women in the labor market. These findings can be supported by the results of a study conducted in Curitiba, PR, in which the mother's routine with the child proved to be paramount for the maintenance of breastfeeding, identifying that nursing mothers were able to maintain breastfeeding due to the fact that they worked outside the home; however, the difficulty found was to maintain exclusive breastfeeding.…”
Section: Discussionmentioning
confidence: 99%